Russell J. Mueller papers - Mueller, Russell J.
Legislation, topical files, newspaper clippings, articles, press releases, printed matter, reports, analyses, and miscellaneous materials related to national health care legislation and associated pension, insurance, and taxation issues and policy. Subjects include consideration by the 103rd Congress (1994-1995) of the Clinton administration's proposed universal health care legislation, Republican efforts in the 104th Congress to amend the Employee Retirement Income Security Act of 1974, and health care and pension policy studies and legislative initiatives in Congress, 1971-1998. House members represented include Harris W. Fawell, William F. Goodling, Steve Gunderson, Thomas E. Petri, and Marge Roukema.
Actuary and congressional staff member. Born 1942.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Clinton, Bill, -- 1946-; Fawell, Harris W. -- 1929-; Goodling, William F. -- 1927-; Gunderson, Steve, -- 1951-; Petri, Thomas E; Roukema, Marge, -- 1929-; United States; Health insurance -- Taxation -- Law and legislation -- United States; Medical policy -- United States; National health insurance -- Law and legislation -- United States; Pension trusts -- Law and legislation -- United States; Pension trusts -- Taxation -- Law and legislation -- United States -- History; Pensions -- Government policy -- United States; Pensions -- Law and legislation -- United States; Taxation -- Law and legislation -- United States; United States -- Politics and government -- 1993-2001.; Actuaries